AL-KAWAKIBI’S PERSPECTIVE ECONOMIC DESPOTISM A STUDY OF THE THABAI’ULIL ISTIBDADI WA-MUSHORI’UL ISTI’BAADI - Rafiqi Rafiqi; Amri Amir; Ahmad Rodoni; Afi Parnawi (Universitas Padjadjaran, 2022)
This dissertation aims to discuss first, as a study of the concept of economic despotism and the impacts that occur as a result of despotism. The second, methods or solutions to reduce economic despotism so that people are not supported in tyranny that destroys social order. The method used in this study is purely qualitative which produces descriptive data in the form of written and oral words from people and observable behavior. While the research source is the written data source of al-Kawakibi’s work namely Thabai’ulil istibdadi wa-mushori’ul isti’baadi and Umm al-Qura. To understand the concept of Istibdad with various derivatives using the method of content analysis or “content study”. This research found/produced that the form of government with one ruler, both individual and oligarchs, who ruled with absolute political power (absolute without limits). The author also supports and supports Monstesquieu’s thesis which states that despotism is the worst thing humans have ever done that must be replaced if they want society to be prosperous and prosperous, one side of this phenomenon can damage the social system to make society’s level not harmonious. Then the writer rejects and refutes Adam Smith’s opinion which states that the free market system is permissible and the government is not entitled to